Adjusting the γ/α2 and Ti2AlC phase on microstructure evolution and improving mechanical properties at room and elevated temperatures with the addition of Ta. (July 2022) - Zhou, Lingyan; Fang, Hongze; Yang, Xiaokang; Chen, Ruirun; Yan, Yongda; Zhang, Yong; Su, Yanqing; Guo, Jingjie
Abstract: Alloys of Ti-46Al-6Nb-2.5C- x Ta (at. %) were prepared to adjust the γ/α2 phase, refine microstructures, and improve mechanical properties at room and elevated temperatures simultaneously. Phase contents, lamellar colony size, Ti2 AlC morphology, compressive and tensile properties, and related mechanisms were discussed. The results show that the relative content of the γ phase increases and the relative content of the α2 phase decreases when Ta content increases from 0 to 2.0 at. %. The solid solution effect of Ta in reinforcing phases contributes to the absence of brittle B2 phase. The content of small length-diameter ratios of Ti2 AlC particles increases. The lamellar colony size decreases from 29.9 to 21.6 μm. The constitutional undercooling and heterogeneous nucleation are increased by Ta during the solidification process. Compressive strength increases from 1974 to 2330 MPa when Ta content increases to 0.8 at. %, and the strain increases from 19.8 to 28.2% when Ta content increases to 1.2 at. %. The tensile strength of the Ti-46Al-6Nb-2.5C-2.0Ta alloy increases from 460 to 503 MPa and its strain increases from 4.1 to 8.3%, when temperature increases from 750 to 950 °C. The refinement of lamellar colonies and Ti2 AlC, solid solution of Ta, and the ratio of γ/α2 are the main reasons for improving mechanical properties of Ti-46Al-6Nb-2.5C-2.0Ta alloy. Highlights: The ratio of γ/α2 was successfully regulated by adjusting the content of Ta element. The Ti2 AlC and lamellar colony are refined because of the constitutional undercooling and the increase of heterogeneous nucleation sites caused by Ta. The compression performance of TiAl composites is improved, the maximum strength is 2330 MPa and the maximum strain is 28.2%. The high temperature properties of TiAl composites is improved, the tensile strength increases from 460 to 503 MPa, and the strain increase from 4.1 to 8.3%, when temperature increases from 750 to 950 °C.